2011
DOI: 10.1136/adc.2009.177527
|View full text |Cite
|
Sign up to set email alerts
|

Health information needs of families attending the paediatric emergency department

Abstract: The authors identified a gap in the provision of health information with respect to appropriate educational material for children and young persons, for families with poor literacy skills and those with language barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
(30 reference statements)
1
20
0
Order By: Relevance
“…The value of safety netting advice has been highlighted by other authors 26 27. Our data would support its value.…”
Section: Discussionsupporting
confidence: 72%
“…The value of safety netting advice has been highlighted by other authors 26 27. Our data would support its value.…”
Section: Discussionsupporting
confidence: 72%
“…As suggested by previous studies, opportunities within practice need to be exploited to empower patients [49]. Opportunities are being lost to inform parents about symptomatic care and when to reconsult.…”
Section: Discussionmentioning
confidence: 95%
“…Better provision is needed for those with low literacy or who are unable to understand written English: a recent study in emergency care reported that 14% of families could not read English [19], which was highlighted as a concern in this study. Previous studies have demonstrated greater knowledge and satisfaction in parents given verbal and written health information, compared to verbal only, when their children were discharged from hospital [20].…”
Section: Discussionmentioning
confidence: 99%